Beaded structured CNTs-Fe3O4@C with low Fe3O4 content as anode materials with extra enhanced performances in lithium ion batteries. Issue 37 (24th March 2015) - Xu, Yuan; Feng, Jingdong; Chen, Xuecheng; Kierzek, Krzysztof; Liu, Wenbin; Tang, Tao; Mijowska, Ewa
Abstract : A simple, effective and reproducible method has been carried out for synthesis of CNT-Fe2 O3 and CNT-Fe3 O4 @C beaded structures for lithium ion battery. Abstract : The present paper reports a facile method to synthesize CNT-Fe2 O3 and CNTs-Fe3 O4 @C beaded structures by deposition of Fe2 O3 and carbon layers on CNTs, which integrate both electronic conductivity and buffering matrix design strategies. The CNT-Fe2 O3 and CNTs-Fe3 O4 @C were tested as anode materials for lithium-ion batteries, CNT-Fe2 O3 showed excellent cycling performance, the reversible capacity retention after 80 cycles is stable at 410 mA h g −1 . However, CNTs-Fe3 O4 @C exhibited improved reversible capacity and better cycling performance when compared to CNT and CNTs-Fe2 O3 . The highly improved reversible capacities are attributed to the combination of (a) the network structured CNTs, which improve the matrix electrical conductivity, (b) the mesopores created by the carbon coating on Fe3 O4 nanoparticles and CNTs, which increases lithium-ion mobility and storage, and (c) the Fe3 O4 nanoparticles attached to the CNTs facilitate the transport of electrons and shorten the distance for Li + diffusion. This study provides a cost-effective, highly efficient method to fabricate nanomaterials which combines carbon nanotubes with iron oxide nanoparticles for the development of lithium ion batteries with high-performance.